Developing the basic futsal skills of fifth grade students By managing learning according to harrow’s Learning instruction model - Marongmeud, Worrawit (Journal for Developing the Social and Community, 2023)
This research aims to 1) to developing learning management for basic futsal skills of fifth grade students, effective students 70/70. 2) to comparison of basic futsal skills of the students with the criteria of 70 percent. 3) to comparison of pre-study and post-study achievement of fifth grade students. The target group used in this research Including 7 students studying in fifth grade, in the second semester, academic year 2021, Ban Nong Khu Khok Pek School, Educational Service Area Office. Roi Et Elementary School District 2, obtained by purposive sampling. The tools used in the research consisted of learning management plan, the test to measure basic skills in the sport of futsal, and achievement test on the development of basic futsal skills of fifth grade students. The results showed that 1) the effectiveness of the developing the basic futsal skills of fifth grade students by managing learning according to harrow’s instruction model has an efficiency of 71.89/82.86, which is higher than the threshold set of 70/70. 2) The fifth grade students who have developed the basic futsal skills by managing learning according to harrow’s instruction model having basic skills in playing futsal after school, 70% higher than the specified criteria, with a statistically significant level of .05 level. 3) The fifth grade students who have developed the basic futsal skills by managing learning according to harrow’s instruction model having the academic achievement after school was significantly higher than before at the .05 level.